Battle of Petersburg, June 15-18, 1864. - Chick, Sean Michael (Potomac Books, 2015)
The Battle of Petersburg was the culmination of the Virginia Overland campaign, which pitted the Army of the Potomac, led by Ulysses S. Grant and George Gordon Meade, against Robert E. Lee's Army of Northern Virginia. In spite of having outmaneuvered Lee, after three days of battle in which the Confederates at Petersburg were severely outnumbered, Union forces failed to take the city, and their final, futile attack on the fourth day only added to already staggering casualties. By holding Petersburg against great odds, the Confederacy arguably won its last great strategic victory of the Civil W.